Frequency of Hepatitis C Virus in People with Tattoos in Diyala Governorate - Rehab Hussein Ibrahim; Luma Taha Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Hepatitis C Virus remains a significant risk worldwide. Tattooing is one of the routes of transmission ofinfection from an infected person to another. Tattooing is a method of injection of exogenous pigments intothe dermis to produce a permanent design. The study aims to detect the frequency of HCV in people withtattoos in the Diyala governorate Iraq. A cross-sectional study was done in the period from 1st October2020 until 15th February 2021 in Baquba teaching hospital (premarital screening program, and periodicexamination of hairdressing salons within the preventive health affairs and consulting clinic). The studyincluding 100 patients (43 were male and 57 female) aged from (10-65 years old). After the preparation ofsamples, an enzyme-linked immunosorbent assay (ELISA) test was performed to detect hepatitis C virusantibodies (IgG). The results of this study showed that the frequency of Hepatitis C Virus 17% (17 out of100) with highly significant differences (p< 0.05), for age group HCV positivity, constituted the highestpercentage rate of age groups between (31-40 years old) followed by (21-30 years old) with a percentage(58.8% and 41.2%) respectively with no significant differences between age groups and Hepatitis C virusinfection on study population (p> 0.05). Depending on the gender, it was found that males with HCV formedthe highest percentage rate (76.50%) compared to females (23.50%), with highly significant differences (p>0.05). Depending on the education level, it was found the secondary graduated had a higher incidence ofHCV (52.9%) compared to primary and college graduates (41.2%) with no significant differences (p> 0.05)while for the diseases, it was found that people without diseases formed the highest percentage rate of tattoocarriers (64.9%) as compared to the presence of diseases with significant differences (p> 0.05). This studyconcludes that HCV is transmitted by tattoos, especially not recommended centres, and in salons lacking theminimum hygienic requirements.